The relationship between job safety, safety programme and policies and management safety practices towards safety behavior among academicians in Management and Science University, Shah Alam, Selangor - Eddy, Abdul Raub (2018)
This study examines the relationship between job safety, safety program and policies and management safety practices towards safety behavior among academicians in Management and Science University, Shah Alam, Selangor. A total of 230 questionnaires were distributed to participants who had agreed to participate in this study. The entire 230 questionnaire were returned and usable for further analyses. Hypotheses for direct effect were tested using multiple regression analyses. The major findings of the study have indicated that two independent variables, i.e. job safety and safety programmes policies influenced significantly the compliance safety behavior. On the other hand, management safety practices were not significantly related to compliance safety behavior of the academicians in Management and Science University. Implications of the findings, potential limitations, and directions for future research were discussed.